Who gains from rubber research? - Wong, W. M.; Chew, T. A.; Omar, Ishak (Malaysian Agricultural Economics Association, 1984)
The distribution of social benefits which arise from rubber research between producers and consumers is determined using Akino-Hayami and Hertford-Schrnitz formulae. Some preliminary results indicate that at least a quarter of research benefits goes to consumers